1998
DOI: 10.1159/000013345
|View full text |Cite
|
Sign up to set email alerts
|

Immunoallergic Granulomatous Interstitial Nephritis following Treatment with Omeprazole

Abstract: A 69-year-old male who had a long history of ocular myasthenia was treated with omeprazole for 3 months. Progressive renal insufficiency was discovered fortuitously. There were no clinical or laboratory manifestations of immunoallergy. Renal biopsy revealed severe granulomatous interstitial nephritis, tubular injury and fibrosis. Histology of a liver nodule disclosed hepatic granulomatous involvement. Withdrawal of omeprazole and a short course of corticosteroids were followed by improvement but not normalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Even in the presence of hypercalcaemia, plasma levels of vitamin D are not always high, as in the case presented here [1,15]. Omeprazole has been involved in certain reported cases of immunoallergic GIN [21]. Hypercalcaemia is typically absent.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Even in the presence of hypercalcaemia, plasma levels of vitamin D are not always high, as in the case presented here [1,15]. Omeprazole has been involved in certain reported cases of immunoallergic GIN [21]. Hypercalcaemia is typically absent.…”
mentioning
confidence: 59%
“…Unlike sarcoidosis-induced GIN, there is no proof that prednisone is effective. Withdrawal of the drug is usually enough to reverse the inflammatory process [21]. In our patient, omeprazole was not discontinued and the prednisone therapy returned calcaemia to normal with considerable improvement in renal function.…”
mentioning
confidence: 69%
“…Following a recent rise in the use of PPIs, a number of individual case reports, case series and commentaries of PPI‐induced acute interstitial nephritis have been reported in the literature 9–49 . This has alerted the medical community to this serious complication and has placed PPIs among the principal causes of medication‐induced reversible acute renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…It was the first of many that raised the possibility of a causal association between PPI therapy and AKI. Following over a decade of isolated reports, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 2 case series were published in 2006 that systematically investigated the association between PPI therapy and AIN through retrospective review of biopsy reports ( Table 1 ). 36 , 37 The first, a study from Australia, found 18 cases with biopsy-proven AIN in 2 hospitals over a 10-year period.…”
Section: Data Linking Ppi Use and Akimentioning
confidence: 99%